Finance and Income Inequality: A Review and New Evidence - Jakob de Haan; Jan-Egbert Sturm (Center for Economic Studies and ifo Institute (CESifo), 2016)
Using a panel fixed effects model for a sample of 121 countries covering 1975 ]2005, we examine how financial development, financial liberalization and banking crises are related to income inequality. In contrast with most previous work, our results suggest that all finance variables increase income inequality. The level of financial development conditions the impact of financial liberalization on inequality. Also the quality of political institutions conditions the impact of financial liberalization on income inequality, in contrast to the quality of economic institutions. Our main findings are robust for using random effects, cross ]country regressions and legal origin as instrument for financial development.
Keywords: D31; D63; F02; O11; O15; 330; income inequality; financial liberalization; financial sector size; financial crises; political institutions